1985
DOI: 10.1161/01.res.57.1.74
|View full text |Cite
|
Sign up to set email alerts
|

Passage of ions and dextran molecules across the rete mirabile of the eel. The effects of charge.

Abstract: SUMMARY. The countercurrent-perfused rete mirabile of the eel is a preparation in which capillary permeability values can be determined accurately in broadscale fashion. To provide insight into charge effects on transendothelial passage, the permeability values of small inorganic cations (labeled sodium and rubidium, and stable potassium) and anions (labeled chloride, iodide, sulfate, and ferrocyanide) were compared to those expected for neutral solutes with approximately matched diffusion coefficients, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

1987
1987
2002
2002

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 65 publications
2
3
0
Order By: Relevance
“…The charge-dependence in vascular permeability in tumours is consistent with observations in normal tissues (Jain, 1997;Curry et al, 1987;Turner et al, 1983;Vehaskari et al, 1984;Deen et al, 1980;Baldwin et al, 1991;Dermietzel et al, 1983;Adamson et al, 1988;Barrowcliffe et al, 1990;Gandhi and Bell, 1992;Gilchrist and Parker, 1985;Haraldsson et al, 1983;Khaw et al, 1991;Leypoldt and Henderson, 1993;Michel and Phillips, 1985;Öjteg et al, 1987;Parker et al, 1985;Rasio and Goresky, 1985;Triguero et al, 1989), suggesting the luminal surface of tumour vascular endothelium is negatively charged as well.…”
Section: Molecular Charge-dependence Of Vascular Permeabilitysupporting
confidence: 82%
See 1 more Smart Citation
“…The charge-dependence in vascular permeability in tumours is consistent with observations in normal tissues (Jain, 1997;Curry et al, 1987;Turner et al, 1983;Vehaskari et al, 1984;Deen et al, 1980;Baldwin et al, 1991;Dermietzel et al, 1983;Adamson et al, 1988;Barrowcliffe et al, 1990;Gandhi and Bell, 1992;Gilchrist and Parker, 1985;Haraldsson et al, 1983;Khaw et al, 1991;Leypoldt and Henderson, 1993;Michel and Phillips, 1985;Öjteg et al, 1987;Parker et al, 1985;Rasio and Goresky, 1985;Triguero et al, 1989), suggesting the luminal surface of tumour vascular endothelium is negatively charged as well.…”
Section: Molecular Charge-dependence Of Vascular Permeabilitysupporting
confidence: 82%
“…Thus, it restricts the extravasation of anionic macromolecules, as has been demonstrated in cultured endothelial cell monolayer (Sahagun et al, 1990) and various normal tissues (Jain, 1997;Curry et al, 1987;Turner et al, 1983;Vehaskari et al, 1984;Deen et al, 1980;Baldwin et al, 1991;Dermietzel et al, 1983;Adamson et al, 1988;Barrowcliffe et al, 1990;Gandhi and Bell, 1992;Gilchrist and Parker, 1985;Haraldsson et al, 1983;Khaw et al, 1991;Leypoldt and Henderson, 1993;Michel and Phillips, 1985;Öjteg et al, 1987;Parker et al, 1985;Rasio and Goresky, 1985;Triguero et al, 1989). Adamson et al (1988) have demonstrated that the microvascular permeability to α-lactalbumin (M r = 14 176, net charge -10) is approximately 50% of that to ribonuclease (M r = 13 683, net charge +4), suggesting that the microvascular permeability to the positively charged molecules is higher than the permeability to the negative ones.…”
mentioning
confidence: 95%
“…No data have been reported on measurement of the iodide space, although our values are rather higher than the chloride spaces reported by Villamil et a f and Headings eta1.2' This is consistent with the results of our direct comparison of Iand C1uptake in different tissue preparations and may in part be due to the formation of the highly lipid-soluble 13ion. 28 The effects of cyanide poisoning on monovalent anion distribution' are qualitatively similar to those we found after freezing and thawing. We are not aware of any previous work on the effect of changing ionic strength on ionic uptake, other than the work of Hudgins on Ca++, which shows a large increase at low ionic strengths very similar in magnitude to that which we observed.…”
Section: Discussionsupporting
confidence: 75%
“…This space is likely to be filled by a matrix of fibrous molecules, with associated charge effects. 35 Our observation that ionic transport is reduced in the rete capillaries by comparison with neutral solutes with similar diffusion coefficients 36 is consonant with this idea. Alterations of the matrix density or charge during hypoxia could potentially account for changes in small solute permeability without visible widening of interendothelial junctions.…”
Section: Discussionmentioning
confidence: 57%